Sero-antigen prevalence of lymphatic filariasis and risk factors of podoconiosis in Busiriba sub-county, Kamwenge district, Southwestern Uganda, August–September 2018 - Mwesigye, Vicent; Musinguzi, Benson; Okongo, Benson; Mucunguzi, William; Kakaire, Michael Nyende; Migisha, Richard (BioMed Central Ltd, 2024)
Abstract Given the neglected nature of filariasis, especially in Uganda where data are scarce, this cross-sectional study aimed to determine the sero-antigen prevalence of lymphatic filariasis and risk factors associated with non-lymphatic filariasis (podoconiosis) in Busiriba Sub-county, Kamwenge District, Uganda, during August-September 2018, to inform targeted elimination efforts. We enrolled 101 participants, among whom 35 (34.7%) had podoconiosis. The sero-antigen prevalence of lymphatic filariasis was 1.0%. Older age and walking barefoot were associated with increased podoconiosis risk. Specifically, individuals aged 25-49 years with had 7.38 times higher odds of podoconiosis (adjusted odds ratio [aOR] = 7.38, 95% CI: 1.36-40.13) compared to those under 25 years, while those aged ≥ 50 years had even higher odds (aOR = 8.49, 95%CI: 1.44-50.15). Additionally, individuals who reported walking barefoot had 14 times higher odds of podoconiosis (aOR = 14.08; 95% CI: 2.49-79.50).
Keywords: Filariasis, Podoconiosis, Lymphatic filariasis, Bancroftian elephantiasis, Uganda